P117 INCIDENTAL FINDING OF A PAPILLARY FIBROELASTOMA WITH UNCOMMON LOCATION: CASE REPORT. (18th May 2022) - Salvatore, T; Ceriello, L; De Rosa, M; Lavorgna, A; Ruggieri, B; Giancola, R; Fabiani, D; Napoletano, C
Abstract: : A 64–year old man with no cardiological history came to our laboratory to perform a transthoracic echocardiogram because of increased blood pressure. Patient was asymptomatic. Echocardiogram revealed the presence of a small mass attached to the proximal part of the interventricular septum (IVS) (Fig. 1 ), characterized by high mobility within the left ventricular outflow tract (LVOT). Transesophageal echocardiogram confirmed the presence of a 8 mm pedunculated mass with implant base on IVS, 2 cm below the aortic valve and oscillating in LVOT (Fig. 2 ). The high risk of peripheral embolization led the Heart team to propose cardiac surgery. The operation was conducted through a J–ministernotomy on a fourth intercostal space, cannulation of ascending aorta and right atrium, transverse aortotomy and identification of the mass via the transaortic route. The appearance of the mass, glossy brown and with a gelatinous consistency, first appeared to be attributable to papillary fibroelastoma. The histological investigation (Fig. 3 ) confirmed the diagnosis. Postoperative course was regular and the patient was discharged on fifth postoperative day. Discussion: Papillary fibroelastoma is the third most common primary cardiac tumour, after myxoma and lipoma, with an incidence of around 10%. In 90% of the cases the origin is from the valvular endocardium (the aortic and mitral valve surfaces are the most affected sites), while the origin from the endocardium of left ventricle, as in the case of our patient, is much more rare (less than 10% of cases). Atypical locations, in addition to IVS, are papillary muscles, tendinous chords and atrial endocardium. Although most patients are asymptomatic, consequences related to peripheral embolization can be very serious (neurological complications, acute coronary sindrome, peripheral ischaemia, pulmonary embolism). Mobility rather than size appears to be an indipendent predictor of death and non fatal embolization; for this reason, in the presence of mobile and pedunculated mass, surgical intervention is always reccomended. Surgical excision is associated with a low operative risk and the minimally invasive approach, as in our case, allows for a rapid recovery.